2016
DOI: 10.1111/1462-2920.13268
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resistance to linalool in Salmonella Senftenberg and their role in survival on basil

Abstract: Fresh produce contaminated with human pathogens raises vital and ecological questions about bacterial survival strategies. Such occurrence was basil harboring Salmonella enterica serovar Senftenberg that caused an outbreak in 2007. This host was unanticipated due to its production of antibacterial substances, including linalool. We show that linalool perforates bacterial membranes, resulting in increased permeability and leakage of vital molecules. It also inhibits cell motility and causes bacterial aggregatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 78 publications
2
34
0
Order By: Relevance
“…It was shown that linalool perforates the bacterial membrane of Gram-negative bacteria, resulting in the increased permeability of both membranes and the leakage of vital molecules (16). Linalool also directly or indirectly inhibits cell motility and causes bacterial aggregation in Salmonella enterica serovar Senftenberg by an unknown mechanism (16,17). The MIC of linalool against pathogens like Escherichia coli, Salmonella enterica, Staphylococcus spp., and Streptococcus spp.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It was shown that linalool perforates the bacterial membrane of Gram-negative bacteria, resulting in the increased permeability of both membranes and the leakage of vital molecules (16). Linalool also directly or indirectly inhibits cell motility and causes bacterial aggregation in Salmonella enterica serovar Senftenberg by an unknown mechanism (16,17). The MIC of linalool against pathogens like Escherichia coli, Salmonella enterica, Staphylococcus spp., and Streptococcus spp.…”
mentioning
confidence: 99%
“…typically ranges from 0.6 to 125 mM (17,18). However, much of the commercial use of linalool involves preparations with unspecified concentrations of linalool which may fall into its sublethal dosage range and, hence, provide considerable opportunity for bacterial adaptation to linalool (higher MIC values) when other barriers to bacteria applied in the product are not sufficient to eliminate the pathogens (16). For example, commercial fruit juices contain 0.02 to 90 mM linalool (19), and pet feed may contain up to 0.6 mM linalool (20).…”
mentioning
confidence: 99%
See 3 more Smart Citations